SABTU CERIA: MERESPONS KEBUTUHAN PENDIDIKAN ROHANI INTERAKTIF BAGI ANAK-ANAK DI LINGKUNGAN GKSI EFRATA - Laoli, Antonius (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
Gereja Kristen Setia Indonesia (GKSI) Jemaat Efrata, located in the East Jakarta area, Jln. Kalimantan No. 18. This is where the implementation of this Community Service activity was held. Based on observations of the results and surveys conducted, spiritual activities for children, especially in the Ephrata congregation GKSI environment, still have not been carried out because children prefer to play games and lack of concern from parents or teachers to take part in children's spiritual life interactively. As a form of responsibility and concern, the implementer of this Community Service is present as an answer to these needs. The goal is that children in the GKSI Jemaat Efrata environment live in a better spiritual life, understand the truth of God's word based on application through media, and children become a generation that fears God and has noble character. The implementation of this Community Service uses the methods of observation, survey, discussion, and is supported by literature study. The results obtained from this effort are that the children in the GKSI Jemaat Efrata environment already have an understanding and knowledge of how to be a responsible person and live in fear of God.